Karakteristik Individu Perilaku Komunikasi dan Penggunaan Jenis Media dengan Pemahaman Petani Tentang Kredit Ketahanan Pangan (Kasus Kelompok Tani di Tanggamus) - Anna Gustina (Jurnal Ilmiah ESAI, 2010)
The success of Credit Resilience Food program (KKP) has been the Governmental cymbal since year 2001. Its target is to guarantee the availability of food (rice). Liquidation Indonesian Bank credit facility (BLBI) program has to be comprehended better by all farmers so that it would be exploited more optimally. Based on the experience of management, the credit of farm faces communication distortion as the biggest problem. It includes individual characteristic factor, communication behavior, and media type which is used in adopting food resilience credit program information (KKP). This research is to know the factors related to understanding of farmer about the KKP. This research used descriptive correlative method from March to August 2007. The result indicates that there is real relation among individual characteristic, communication behavior, and media type use, with understanding of farmer about KKP program. Key words : Credit Resilience food program, farmers understanding, Communications Credit Resilience food program, Understanding of farmers, Communications